Metformin and the risk of dementia based on an analysis of 396,332 participants - Shiliang Ji; Xingxing Zhao; Ruifang Zhu; Yongchao Dong; Lifeng Huang; Taiquan Zhang (SAGE Publishing, 2022)
Background: AMPK has attracted widespread interest as a potential therapeutic target for age-related diseases, given its key role in controlling energy homeostasis. Metformin (Met) has historically been used to treat Type 2 diabetes and has been shown to counteract age-related diseases. However, studies regarding the relationship between Met and a variety of age-related classifications of cognitive decline have reported mixed findings. Objective: To assess the potential effect of Met on the onset of dementia and discuss the possible biological mechanisms involved. Methods: This study was registered in the PROSPERO database (CRD420201251468). PubMed, Embase, and Cochrane Library were searched from inception to 25 May 2021, for population-based cohort studies. Effect estimates with 95% confidence intervals (CIs) were pooled using the random-effects model. Meta-regression and subgroup analyses were performed to explore sources of heterogeneity and the stability of the results. Results: Fourteen population-based cohort studies (17 individual comparisons) involving 396,332 participants were identified. Meta-analysis showed that Met exposure was significantly associated with reduced risk of all subtypes of dementias [relative risk (RR) = 0.79, 95% CI = 0.68-0.91; p  < 0.001]. Conversely, no significant reduction in risk was observed for those who received Met monotherapy at the onset of vascular dementia (VD), Parkinson's disease (PD), and Alzheimer's disease (AD). The effect was more prominent in patients who had long-term Met exposure (⩾4 years) (RR = 0.38, 95% CI = 0.32-0.46; p  < 0.001), while no such significant effect was found with short-term Met exposure (1-2 years) (RR = 1.20, 95% CI = 0.87-1.66; p  < 0.001). Moreover, no association was observed for Met exposure in participants of European descent (RR = 1.01, 95% CI = 0.66-1.54; p  = 0.003) compared with those from other countries. Conclusion: Based on the evidence from population-based cohort studies, our findings suggest that the AMPK activator, Met, is a potential geroprotective agent for dementias, particularly among long-term Met users. Due to the significant heterogeneity among the included studies, we should interpret the results with caution.